Human mesenchymal stem cells attenuate pulmonary hypertension induced by prenatal lipopolysaccharide treatment in rats. (October 2016) - Chou, Hsiu‐Chu; Lin, Willie; Chen, Chung‐Ming
Summary: Intra‐amniotic injection of lipopolysaccharide (LPS) induces pulmonary hypertension in newborn rats. This study was designed to test whether human mesenchymal stem cells (MSCs) reduce pulmonary hypertension and alleviate cardiac hypertrophy in prenatal LPS‐treated rats. Pregnant Sprague‐Dawley rats were injected intraperitoneally with LPS (0.5 mg/kg per day) or untreated on gestational days 20 and 21. Human MSCs (3×10 5 cells and 1×10 6 cells) in 0.03 mL of normal saline (NS) were transplanted intratracheally on postnatal day 5. Four study groups were considered: normal, LPS+NS, LPS+MSCs (3×10 5 cells), and LPS+MSCs (1×10 6 cells). On postnatal day 14, lung and heart tissues were collected for measuring the arterial medial wall thickness (MWT) and β‐myosin heavy chain (β‐MHC) level as markers of pulmonary hypertension and cardiac hypertrophy, respectively. The LPS+NS group exhibited a significantly higher right ventricle (RV)/[left ventricle (LV)+ interventricular septum (IVS)] thickness ratio and MWT, a greater cardiomyocyte width, a greater number of cardiomyocyte nuclei per squared millimeter, and higher β‐MHC expression than those observed in the normal group. Human MSC transplantation (3×10 5 cells and 1×10 6 cells) in LPS‐treated rats reduced MWT and the RV/(LV+IVS) thickness ratio to normal levels. This improvement in right ventricular hypertrophy was accompanied by a decrease in toll‐like receptor 4 (TLR4), nuclear factor‐κB, and tumor necrosis factor‐α expression in the heart. Intratracheal human MSCs transplantation can attenuate pulmonary hypertension and right ventricular hypertrophy in prenatal LPS‐treated rats; this attenuation may be associated with suppression of TLR4 expression via paracrine pathways.